Your baby doesn't come with a book : Dr. Golly's guide to the first four weeks of parenthood - Golshevsky, Daniel (Collingwood VIC : Hardie Grant Books, 2025)
Dr Daniel Gloshevsky's (also known as Dr Golly) guide to caring for your baby from before the birth to the first 4 weeks after birth.
Includes index.
Keywords: Infants -- Care; Infants -- Development; Newborn infants -- Care; Postnatal care